Protective Effect of Selenium-Based Medicines on Toxicity of Three Common Organophosphorus Compounds in Human Erythrocytes In Vitro - Fakhri-Bafghi, Maryam Sadat (Cell J, 2016)
OBJECTIVE: Organophosphorus (OP) compounds are used to control pests, however they can reach the food chain and enter the human body causing serious health problems by means of acetylcholinesterase (AChE) inhibition and oxidative stress (OS). Among the OPs, chlorpyrifos (CHP), malathion (MAL), and diazinon (DIA) are commonly used for commercial extermination purposes, in addition to veterinary practices, domestic, agricul- ture and public health applications. Two new recently registered medicines that contain selenium and other antioxidants, IMOD and angipars (ANG), have shown beneficial ef- fects for OS related disorders. This study examines the effect of selenium-based medi- cines on toxicity of three common OP compounds in erythrocytes. MATERIALS AND METHODS: In the present experimental study, we determined the ef- ficacy of IMOD and ANG on OS induced by three mentioned OP pesticides in human erythrocytes in vitro. After dose-response studies, AChE, lipid peroxidation (LPO), total antioxidant power (TAP) and total thiol molecules (TTM) were measured in eryth- rocytes after exposure to OPs alone and in combined treatment with IMOD or ANG. RESULTS: AChE activity, TAP and TTM reduced in erythrocytes exposed to CHP, MAL and DIA while they were restored in the presence of ANG and IMOD. ANG and IMOD reduced the OPs-induced elevation of LPO. CONCLUSION: The present study shows the positive effects of IMOD and ANG in re- duction of OS and restoration of AChE inhibition induced by CHP, MAL and DIA in erythrocytes in vitro.